2016
DOI: 10.1002/star.201600077
|View full text |Cite
|
Sign up to set email alerts
|

QTL mapping of the pasting properties of wheat flour treated by papain digestion

Abstract: Protein hydrolysis is widely used in the food industry to improve food or industrial quality, and processing is carried out concurrently or subsequently to starch pasting. In this study, QTL mapping of the pasting properties of natural wheat flour (NWF) and papain‐treated flour (PTF) was performed in three environments. These analyses involved a set of 173 F9:10 recombinant inbred lines (RILs) derived from “Shannong01‐35 × Gaocheng9411” with a genetic linkage map consisting of 6248 molecular markers. The addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Furthermore, a major QTL for SC‐SRC, QSc4B.4‐13 , was also located within this colocated chromosomal interval associated with IACX557 (28,954,114). Previous studies have reported QTLs for kernel protein (Liu, Liu et al., 2017), steamed bread textural properties (Liu, An et al., 2017), and flour pasting properties (Wang et al., 2016) flanking IACX557 . Interestingly, IACX557 is located near known genes such as LoxA/B for yellow pigment content (27.5 Mb), Rht‐B1 for plant height (∼30.861 Mb), and FLO6 for starch synthesis (21.937 Mb).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a major QTL for SC‐SRC, QSc4B.4‐13 , was also located within this colocated chromosomal interval associated with IACX557 (28,954,114). Previous studies have reported QTLs for kernel protein (Liu, Liu et al., 2017), steamed bread textural properties (Liu, An et al., 2017), and flour pasting properties (Wang et al., 2016) flanking IACX557 . Interestingly, IACX557 is located near known genes such as LoxA/B for yellow pigment content (27.5 Mb), Rht‐B1 for plant height (∼30.861 Mb), and FLO6 for starch synthesis (21.937 Mb).…”
Section: Discussionmentioning
confidence: 99%
“…QSsv.cau-4B.1 and QSsv.cau-4D was located next to the dwarf genes Rht-B1 and Rht-D1, respectively. Previous studies have also revealed QTL-enrichment areas near Rht-B1 and Rht-D1, which are associated with kernel size, kernel hardness, kernel protein, pasting properties, and mixing properties (Shanhong et al, 2001;Li et al, 2006;Wang et al, 2012Wang et al, , 2017Patil et al, 2013;Zhang et al, 2013;Jin et al, 2016;Liu et al, 2017b).…”
Section: Novel Quantitative Trait Locus For Sodium Dodecyl Sulfate-sedimentation Volumementioning
confidence: 98%
“…A combination of RFLP, SSR, and Amplified Fragment Length Polymorphism (AFLP) was also used to increase the marker density in maps ( Table 1 ) ( Sourdille et al, 2003 ; Mohler et al, 2014 ). With the advancement in sequencing technologies, the use of SNP has been prioritized since they are abundant and uniformly distributed in a genome providing high genomic resolution ( Gupta et al, 2008 ; Kang et al, 2016 ; Wang et al, 2017 ; Naraghi et al, 2019 ; Guo Y. et al, 2020 ). The availability of high throughput sequencing platform for SNPs makes it a preferred genotyping method in general.…”
Section: Genetic and Genomic Studies On Wheat End-use Quality Traits:...mentioning
confidence: 99%